PROFIL KOMPETENSI GURU BIOLOGI SMA NEGERI KOTA PEKANBARU DALAM MENERAPKAN PENELITIAN TINDAKAN KELAS (PTK) - Yustina "; Ranti Octavia; Mariani Natalina (Biogenesis, 2016)
ABSTRACT The aim of this study was to describe competence of biology teachers at public senior high school pekanbaru on action research. This study hold on Desember 2015 until March 2016. The sample of this study was 29 biology teachers at Public Senior High School in Pekanbaru that selected by purposive sampling. This study conducted with closed-ended and open–ended questionnaire. The closed-ended questionnaire consist of 17 items and divided into 3 indicator. The indicator are motivation, Information and Communication Technology (ICT) skill and then 42 item about Class action Reset included 4 indicator. The indicatore are (Device class action research, backgroundclass action research, Implementation and Results class action research). The whole item questionnaire enclosed declared valid and reliable. Closed questionnaire obstacle teachers through Pearson correlation test, where all items declared valid, reliability test questionnaire through Cronbach's alpha test alpha of 0.89 was obtained. Validity and reliability were analyzed using SPSS (Statistical Package for Social Studies) v ersion17.00f or Windows. Whereas the questionnaire reliability test comprehension test values obtained using 4.9 anates 0.9. Data were analyzed descriptively. Overview obstacles Biology teacher SMA Pekanbaru in envolving the action research as follows: Motivation show sufficient criteria with a mean 3.01, ICT Skills showed sufficient criteria to average 3.39. While understanding class action research also showed sufficient criteria with the average percentage of 61.87%. Thus, it is known that the High School Biology teacher Pekanbaru action research implementation by category quite well. Key Words: Teacher competence, Action research, Senior high school,Biology teacher